Programa Bolsa Família: uma análise regional da evolução dos indicadores da pobreza relativa no Brasil - Simone Torres Gusmão Santos (2017)
This dissertation aimed at analyzing the Bolsa Família Program and its contributions to reducing relative poverty in Brazil through the study of its indicators. The period defined for the research was the period from 2011 to 2015 and took place regionally. In order to organize the study, it started from research in the various literatures that deal with the subject. It seeks to understand the phenomenon of poverty from the historical and economic perspective. Through classical authors, we sought to present the unilateral perspective of poverty to contemporaries who discuss the multidimensional vision of poverty. A historical analysis was presented, where economic and social issues that pervade poverty in Brazil are addressed. Next, we seek to understand the Bolsa Família Program through its normative, economic aspects and their impacts. The research was characterized as quantitative-qualitative exploratory. For the collection of statistical data, the National Survey by Household Sample database and the Transparency Portal were used. The data were treated using statistical methods with descriptive analysis and regression models. The data were presented through the panel typology with multiple linear regression model for the twenty - six states and the Federal District. After analyzing the data, there is a concentration of both extreme and relative poverty in the North and Northeast regions of Brazil. On the other hand, the transfers of the Bolsa Família Program have been progressively carried out, with the highest values being transferred to the North and Northeast regions. Regarding the contribution of the Bolsa Família Program to the reduction of relative poverty, it has not been sufficiently developed individually to reduce it, since other policies are necessary for more positive results.